Effects of prepartum whole cottonseed or whole raw soybean supplementation on response to timed artificial insemination in suckled mature beef cows following ovulation synchronization - Thomas, Melissa Deann (Kansas State University, 2008)
Prepartum fat supplementation has been associated with improved reproductive performance by cows managed for AI. Our objective was to evaluate the effects of prepartum supplementation with whole cottonseed or whole raw soybeans on response to ovulation synchronization and timed artificial insemination in mature beef cows. Cows (n = 188; average initial BW = 579 [plus or minus] 54 kg) were stratified by BCS and BW and assigned to 3 supplementation treatments: whole raw soybeans (21.6 % fat, 38.6% CP), whole fuzzy cottonseed (21.7% fat, 21.1% CP), or a 50:50 mixture of ground corn and soybean meal (2.6% fat, 30.6% CP). Supplements were fed at 1.8 kg per animal daily for 45 d before the first projected calving date (April 1). Supplementation was continued until each cow calved; thereafter, all cows received the control supplement until May 1. Ovulation was synchronized using the CoSynch + CIDR protocol and cows were bred via AI on June 21. Eleven d after AI, cows were exposed for natural service breeding for 50 d. Conception to AI was assessed 33 d after AI. Overall conception was assessed and conception to AI reaffirmed 126 d after AI. Body weight of cows fed control or oilseed supplements was similar (P > 0.3) at calving, initiation of ovulation synchronization, and at the end of the breeding season. Cottonseed-supplemented cows lost more BW and more BCS (P < 0.03) from the beginning of the trial to calving than those fed soybeans. Proportion of cycling cows was similar (P = 0.57) between treatments. Pregnancy to timed AI and final pregnancy rates were similar (P > 0.75) between control and oilseed-supplemented cows. Conversely, supplementation with cottonseed was associated with increased AI conception (P = 0.08; 54 and 39%, for cottonseed and soybeans, respectively) and greater final pregnancy rate compared to soybean-fed cows (P = 0.03; 100 and 93% for cottonseed and soybeans, respectively). Calf birth weights and calf weights at the end of the breeding season were similar (P > 0.24) between treatments. Effects of cottonseed and soybean supplementation on response to ovulation synchronization and timed AI by beef cows warrant further study.
Keywords: conception rate; beef cows; fat supplementation; Agriculture, Animal Culture and Nutrition (0475)